МЕТОДИКА РАБОТЫ С НОТНЫМ РЕДАКТОРОМ SIBELIUS - Абылова, Г.Ж. (SCIENCE and SOCIETY, 2016)
The article deals with the effectiveness of the introduction of new information technologies and software in educational musical directions. The author gives the description of using the stave editor Sibelius in the educational process and its importance for students and teachers.